Development of methodology of organisational innovation management: structural modelling of the results - V. V. Degtyareva (Вестник университета, 2025)
The article proposes a structural model for evaluating performance of large industrial companies, built through the effects of influence of three indicator groups: innovation management, sustainable development, economic/investment efficiency. The purpose of the study is to develop a methodology for organisational innovation management with a focus on socially and environmentally responsible innovations. Large industrial corporations, on the basis of which innovation and implementation activities are conducted, are the object of the study. A structural model for evaluating results is the subject of the work. The indicators of non-financial reporting are analysed in the context of growth of business reputation, innovation management, and economic and investment efficiency of two industrial corporations. Based on the identified time series trends of the analysed indicators and conclusions from previous studies, we have proven the hypothesis about the impact of the non-financial reporting in the context of innovation management on the economic and investment efficiency of an industrial corporation. The conclusions drawn in the form of the proposed structural model for evaluating the activities of the research object provide prerequisites for the development of the methodology of the organisational innovation management in the framework of the proactive side of its presentation aimed at increasing corporate budget in order to bring more promising innovative products or services to the market in the context of responsible consumption and sustainable development.